2016
DOI: 10.3847/0004-637x/832/2/182
|View full text |Cite
|
Sign up to set email alerts
|

SDSS-IV MaNGA: A SERENDIPITOUS OBSERVATION OF A POTENTIAL GAS ACCRETION EVENT

Abstract: The nature of warm, ionized gas outside of galaxies may illuminate several key galaxy evolutionary processes. A serendipitous observation by the MaNGA survey has revealed a large, asymmetric Hα complex with no optical counterpart that extends ≈ 8 ′′ (≈ 6.3 kpc) beyond the effective radius of a dusty, starbursting galaxy. This Hα extension is approximately three times the effective radius of the host galaxy and displays a tail-like morphology. We analyze its gas-phase metallicities, gaseous kinematics, and emis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…The local stellar mass surface density is a result of the local galactic stellar assembly history (Yozin & Bekki 2016; Goddard et al 2017a,b;Jones et al 2017), the strong correlation for Σ * -Z can be naturally explained by noticing that the higher Σ * (denser) regions usually locate in the inner region of galaxies (Johnston et al 2017), which have longer star formation history than the less dense regions with lower Σ * (Ibarra-Medel et al 2016). Furthermore, the global stellar mass reflects the assembly of the stellar mass and the depth of the potential wells, which dominates the infall of metal-poor gas and the outflows of metal-rich gas (Peeples & Shankar 2011;Pan et al 2015;Cheung et al 2016;Lian et al 2018). As proposed by Tremonti et al (2004) and Lian et al (2018), the deep gravitational potential wells of massive galaxies retain the processed metals, leading to a higher local metallicity than less massive galaxies even at a similar Σ * .…”
Section: The Impact Of Metallicity Calibratorsmentioning
confidence: 96%
“…The local stellar mass surface density is a result of the local galactic stellar assembly history (Yozin & Bekki 2016; Goddard et al 2017a,b;Jones et al 2017), the strong correlation for Σ * -Z can be naturally explained by noticing that the higher Σ * (denser) regions usually locate in the inner region of galaxies (Johnston et al 2017), which have longer star formation history than the less dense regions with lower Σ * (Ibarra-Medel et al 2016). Furthermore, the global stellar mass reflects the assembly of the stellar mass and the depth of the potential wells, which dominates the infall of metal-poor gas and the outflows of metal-rich gas (Peeples & Shankar 2011;Pan et al 2015;Cheung et al 2016;Lian et al 2018). As proposed by Tremonti et al (2004) and Lian et al (2018), the deep gravitational potential wells of massive galaxies retain the processed metals, leading to a higher local metallicity than less massive galaxies even at a similar Σ * .…”
Section: The Impact Of Metallicity Calibratorsmentioning
confidence: 96%
“…However, Cheung et al (2016b) have found a galaxy in the middle of a gas accretion event, providing a detailed look at what appears to be a relatively rare occurrence in the nearby universe of this mode of galaxy growth. They present serendipitous observations of a large, asymmetric Hα complex that extends ∼8″ (∼6.3 kpc) beyond the effective radius of a dusty, starbursting galaxy.…”
Section: Gas Physicsmentioning
confidence: 99%
“…Interestingly, X3 is a large star forming region, however it has a velocity which is very different (about 400 km/s) from the disc as seen in the stellar velocity profile (due to poor Hα SNR of the host galaxy the velocity map is not visible). It is possible that this galaxy may have undergone a recent merger with a galaxy which may have left a tidal tail or there has been a recent event of gas accretion as in the case of Cheung et al (2016). Given that there is such a high velocity difference, it is also possible that the Hα emission is not associated with HX3, and is rather associated with a neighbouring galaxy (SDSS ObjID: 1237651252560461948), which is about 570 km/s offset from it, which also has an active nucleus.…”
Section: Remarks On Individual Sourcesmentioning
confidence: 99%
“…With the advent of larges scale integral field unit (IFU) surveys e.g., the Mapping Nearby Galaxies at Apache Point Observatory (Bundy et al 2015, MaNGA), Calar Alto Legacy Integral Field Area survey (Sánchez et al 2012, CALIFA), and the Sydney-AAO Multi-object Integral-field spectrograph Galaxy survey (Bryant et al 2015, SAMI) we can now search for such outlying Hα emitters around several thousand galaxies. In the MaNGA survey, Cheung et al (2016) found an outlying Hα complex without any optical counterpart about 6.3 kpc away from the effective radius of the host galaxy and at about 3 times the effective radius of the galaxy. Using a detailed analysis of the gas kinematics, gas phase metallicity, and emission-line ratios the authors argue that the scenario is most consistent with an gas accretion event.…”
Section: Introductionmentioning
confidence: 99%